The Diversity of Macrozoobenthos as a Bioindicator of Water Quality in the Upper Cikapundung River - Kimku, Ancelina; Surtikanti, Hertien Koosbandiah; Suwandi, Tri (-, 2024)
Macrozoobenthos are aquatic organisms that live on the bottom of the water. Currently, the upstream Cikapundung River is indicated to be polluted by garbage, household waste, industrial waste, agricultural waste and livestock manure. This study aims to determine the diversity of macrozoobenthos as a bioindicator of water quality in the upstream Cikapundung river based on physical, chemical and biological parameters. This research was conducted in April 2023. The research used the exploration method. Macrozoobenthos sampling consists of five locations namely; Curug Omas, Curug Lalay, Kidang, Curug Koleang and Curug Dago. The results of the data analysis of the calculation of the Diversity Index, Abundance and Dominance indicate that the upstream Cikapundung river is classified as moderately polluted. This is evidenced by the diversity value obtained, which falls within the range of 1.94 - 2 (2.0). The high abundance index value is observed in location 2, while the dominance index value is 0.50 D ≤ 0.75. A total of nine species were identified in the benthic samples, which were classified into four classes, nine families, and seven genera. The dominating benthos of the five locations is Planaria sp. Based on an analysis of biotic and abiotic components, the upstream Cikapundung river is classified as exhibiting minimal pollution.